Large-Scale Extinction of Large Carnivores (Lion Panthera Leo, Cheetah Acinonyx Jubatus and Wild Dog Lycaon Pictus) in Protected Areas of West and Central Africa. (June 2015) - Brugière, David; Chardonnet, Bertrand; Scholte, Paul
A number of recent studies have suggested that large carnivores are rapidly disappearing in West Africa, including in protected areas (PAs). The extent of this extinction process, however, is poorly known. Here, we quantify the extinction of three large carnivore species ( Panthera leo (lion), Acinonyx jubatus (cheetah) and Lycaon pictus (wild dog)) in 41 West and Central African PAs by comparing historical and current data of occurrence. We found that lions have gone (near-) extinct in 23 out of the 38 PAs (63%) where they historically occurred and that extinction is significantly more pronounced in West (15 extinctions out of 18 historical occurrence, 64%) than in Central Africa (8/20, 40%). Cheetahs have disappeared from 11 out of 15 PAs (73% of site extinction). Wild dogs persist in only one PA in West Africa and two in Central Africa out of a total of 31 historical occurrences (90% of site extinction). For all three species combined, the number of extinctions in PAs in West Africa (33 out of 39 historical occurrences, i.e. 85% of site extinction) is significantly higher than in Central African PAs (29/45, i.e. 64%). Carnivore populations persist outside PAs in that latter region. Our study shows that PAs with remaining lion populations are significantly larger than those with extinct populations. However, we found that the human population density around PAs is not a good predictor of lion extinction. We suggest that the presence of mobile pastoralists may better explain the extinction pattern of large predators, and we recommend developing indicators of the pastoralism pressure to test that hypothesis.